2011
DOI: 10.9710/kjm.2011.27.4.283
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses in Abalone Haliotis discus hannai with Different Salinity

Abstract: This study investigated survival rate, osmorality, respiration, excretion and histological response with change of salinity in the abalone, Haliotis discus hannai at 24 ± 1℃. Survival rate was 100% at 37.0 psu whereas all died after 6 days at 19.8 psu and within 24 hours at 12.8 psu, respectively. The 7-day median lethal limit (7day-LS50) was 20.1-28.2 psu with confidence limits of 20.1-28.2 psu. Respiration rate in low salinity groups was lower than control group, but ammonia excretion rate was more increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 13 publications
0
5
1
1
Order By: Relevance
“…By contrast, at 20 and 25°C, the survival rate by the end of 7 days was 100%, indicating that abalones are more resistant to salinity changes at high temperatures. This contradicts the results of Jeon (2002), who found a negative correlation between water temperature and salinity tolerance of abalone, while Shin et al (2011) and Chen and Chen (2000) obtained the same results as we did. There were no deaths at 30→25 psu, and the survival rates were 70% and 50% at 20 and 15 psu, respectively.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…By contrast, at 20 and 25°C, the survival rate by the end of 7 days was 100%, indicating that abalones are more resistant to salinity changes at high temperatures. This contradicts the results of Jeon (2002), who found a negative correlation between water temperature and salinity tolerance of abalone, while Shin et al (2011) and Chen and Chen (2000) obtained the same results as we did. There were no deaths at 30→25 psu, and the survival rates were 70% and 50% at 20 and 15 psu, respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…Marine organisms respond physiologically to salinity changes in seawater. Environmental changes, including salinity change, cause chemical and physical stress on marine organisms (Holliday et al 1993;Shin et al 2011). Unlike fish, which can move from one place to another with changes in the environment, abalones are gastropods with extremely restricted mobility.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, animals responded to high salinity by increasing their respiration rates and synthesizing new mitochondria, both likely necessary steps to meet the energetic requirements of this acclimation mechanism. Increased respiration rates have also been observed in other osmoconforming invertebrates ranging from mollusks [49] , [50] to echinoderms [51] . Although it is traditionally considered that higher respiration rates are a proxy of energy metabolism, recent studies have shown that it this is not always the case [22] .…”
Section: Discussionmentioning
confidence: 99%
“…However, most sources indicate that osmoconformers have low energetic requirements when exposed to decreased salinity. As salinity increases, their respiration rates also increase (Bouxin, 1931;Navarro and González, 1998;Sarà et al, 2008;Shin et al, 2011;Widdows, 1985;Yu et al, 2013), probably because of the active production of methylamines, FAA and derivates. These organic osmolytes are used by marine osmoconforming molluscs, polychaetes, crustaceans (Goolish and Burton, 1989) and other marine invertebrates such as sipunculids (Peng et al, 1994;Virkar, 1966) to increase intracellular osmolality.…”
Section: Stenohaline Speciesmentioning
confidence: 99%